ANALISIS PENGGUNAAN DEIKSIS TEMPAT DAN WAKTU DALAM NOVEL CINTA BERTABUR DI LANGIT MEKKAH KARYA ROIDAH - Sarifatin, Sarifatin; Rozekki, Rozekki (Jurnal Sastra Aksara, 2019)
This research is entitled "Analysis of the Use of Place and Time Deixis in Cinta Bertabur Di Langit Mekkah Novel by Roidah ". The problem of this research was how to use the place and time deixis in Cinta Bertabur Di Langit Mekkah Novel by Roidah? This research aimed to describe the use of deixis in Cinta Bertabur Di Langit Mekkah Novel by Roidah. The method used was the qualitative descriptive method. Data collection was done by reading the whole novel "Cinta Bertabur Di Langit Mekkah" repeatedly to identify the types of deixis contained in the novel, note-taking all the words or sentences related to the deixis in Cinta Bertabur Di Langit Mekkah novel, giving a sign (underlines) parts of words or sentences in novels related to types of deixis. Data analysis was done by identifying, classifying, analyzing, concluding the results of the analysis. Based on the results of the analysis above, it showed that in Cinta Bertabur Di Langit Mekkah novel, there are two types of deixis such as deixis of place and deixis of time. (1) the deixis of a place was divided into six parts, namely: there, here, there, there, here, and there. (2) deixis of time was divided into six parts, namely: earlier, now, now, yesterday, tonight and first.